A nonlinear relationship between unemployment and human capital - evidence from African countries. (2017) - Abdallh, Atif Awad
This study seeks to examine the validity of the assumption that an increase in the average level of human capital for a country over a specific level will result in replacing workers with technology; and, hence, boost the unemployment rate. Using data for 37 African countries from 2000 to 2013, the present study seeks first: to determine the short and long run effects of human capital accumulation on the unemployment rate in Africa. Second, to identify the threshold level of human capital whereby a further rise will boost unemployment rate in the continent. The results of the Arellano-Bond (A-B) GMM technique showed that the relatively high unemployment rate is due to the continent's excessive human capital accumulation. Most importantly, the magnitude of this effect is likely to be larger in the long run as compared to the short run. These findings imply that Africa's current education expansion policies will result in further increase in the unemployment rate over time.